An empirical analysis of Malaysia rice in the world food market industry / Mohd Firzuan Osman - Osman, Mohd Firzuan (Faculty of Plantation and Agrotechnology, 2017)
Rice is one of the staple food in the world and it consume by majority all population in the world. Rice is the most economically important staple food crop for a large part of the human population, providing more than 3 billion people in Asia with two thirds of their caloric intake, and supplying nearly 1.5 billion people in Africa and Latin America with one third of their caloric needs. Competitiveness determine by analyse the production of paddy based on time series, to determine international trade and analyse price in the world rice market. Sustainability of rice in the world market is to ensure the supply are enough to consumer. Method used to measure is graph analysis by excel, Reveal Comparative Advantage, (RCA), Herfindalf Index, import dependency ratio and self-sufficiency ratio. Result conclude that reveal comparative advantage for Malaysia in rice industry is 0.0071 <1 that mean Malaysia not specialize in rice industry. Herfindalf Index result calculate that the market is 1955 which mean market is high concentration. The average import dependency ratio for Malaysia is 26% which mean the Malaysia not depend much in import trade. The average self-sufficiency ratio indicate that the ratio is 76% which conclude that rice is still enough to the population in Malaysia. The study show that Malaysia do not have much market share in the rice industry in the world, It can concluded that Malaysia need to be more competitive in production and not depend much in import only.